SELF LIGATING BRACKETS AND TREATMENT EFFICIENCY. A CASE REPORT - Panaite Tinela; Romanec Cristian; Dragomir Bogdan; Roxana Chiriac; Chehab Alice; Andreia Ichim; Zetu Irina (Romanian Dental Association for Education, 2023)
This article reports the efficiency of the Damon® self-ligating brackets, for the treatment of a Class II, hypodivergent adult patient. We present a case report of a non-extraction treatment for an adult male patient, and we evaluate the effiency of the treatment by recording the effects obtained over time and comparing them with data from the literature regarding this aspect.